2015
DOI: 10.4067/s0718-381x2015000300024
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Effect of Copper Sulfate on Enterococcus faecalis in Root Canals

Abstract: SÁNCHEZ-SANHUEZA, G.; ALCÁNTARA-DUFEU, R.; CARRILLO, L.; MANSILLA, H.; NOVOA, C.& BELLO-TOLEDO, H. Ex vivo effect of copper sulfate on Enterococcus faecalis in root canal. Int. J. Odontostomat., 9(3):505-510, 2015.ABSTRACT: The incomplete disinfection of root canal system has been reported as the main cause of post-treatment disease, due to the persistence of bacteria. For over thirty years Enterococcus faecalis has been considered the most common bacterial species isolated from persistent root canal infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The sharp contact with metallic copper surfaces did not result in an increase in mutation rates or bacterial DNA lesions (Santo et al, 2011). The starting point for the clinical use of copper, specifically for disinfecting the root canal system is reported in a ex vivo study where the canals treated with copper sulfate pentahydrate showed a reduction of 6 logarithms in the count of colony-forming units on the fourth day (Sánchez-Sanhueza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The sharp contact with metallic copper surfaces did not result in an increase in mutation rates or bacterial DNA lesions (Santo et al, 2011). The starting point for the clinical use of copper, specifically for disinfecting the root canal system is reported in a ex vivo study where the canals treated with copper sulfate pentahydrate showed a reduction of 6 logarithms in the count of colony-forming units on the fourth day (Sánchez-Sanhueza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Innovative endodontic techniques have become widely available over the last years 25,26) in particular, a copper-calcium-hydroxide (Cupral) treatment has been carefully regarded given its potent antimicrobial properties 27) . Not only vegetative forms, but also bacterial spores and viruses were affected, underlying the widerange efficacy such system 27) .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial resistance is a constant concern in the failure of root treatments, hence the importance of studying new antimicrobial agents that can be used as coadjuvants and/or alternatives in endodontic therapy [24]. Copper has multiple properties, among which antimicrobial contact and anti-contact action avoid the appearance of resistant microorganisms and acts as a better antimicrobial dressing than Ca(OH) 2 in the root canal ex vivo model [25]. CuNPs improve the properties of copper as a pure metal, which is a great advantage as they could access tiny dentinal tubules with an average size of 5 µm, in which the endodontic biofilm is housed [15].…”
Section: Discussionmentioning
confidence: 99%